Printing nanoparticle-based isotropic/anisotropic networks for directional electrical circuits. Issue 40 (30th September 2022) - Chen, Sisi; Pan, Qi; Wu, Tingqing; Xie, Hongfei; Xue, Tangyue; Su, Meng; Song, Yanlin
Abstract : An efficient prototype for manufacturing the isotropic/anisotropic circuits is demonstrated through the template-assisted printing strategy, which achieves a remarkable on/off ratio over 10 11 . Abstract : With the demand for integrated nanodevices, anisotropic conductive films are one type of interconnection structure for electronic components, which have been widely used for improving the integration of the system in printed circuit boards. This work presents a template-assisted printing strategy for the fabrication of nanoparticle-based networks with multi electrical properties. By manipulating the microfluid behavior under the guidance of the grid-shaped template, the continuity of liquid bridges can be precisely controlled in two directions. The isotropous circuits with crossbar paths, discrete paths as well as unidirectional paths are obtained, which achieve the switching of on/off states in the circuits. This work demonstrates a new type of directional circuits by the template-assisted printing method, which provides an effective fabrication strategy for electrical components and integrated systems.